EFFECT OF A COMMON UMOD VARIANT ON RENAL FUNCTION, BLOOD PRESSURE, AND FITNESS IN A COMMUNITY-BASED COHORT OF ELDERLY SUBJECTS. (April 2021) - Algharably, Engi Abdel Hady; Fuentes, Linda Elizabeth Villagomez; Toepfer, Sarah; König, Maximilian; Demuth, Ilja; Bertram, Lars; Kreutz, Reinhold; Bolbrinker, Juliane
Abstract : Objective: Uromodulin is encoded by UMOD and common genetic variants in UMOD have been associated with renal function, blood pressure (BP), and hypertension. Observational studies indicated that elevated BP during middle age might be associated with dementia and impaired cognitive function in later life. The aim of this study was to investigate the association of UMOD rs4293393-A>G with renal function, BP, and fitness outcomes in older participants of the Berlin Aging Study II (BASE-II). Design and method: Data for 1556 participants (median age 68 years, range 60–84, 51.2% females) in BASE-II were analyzed. BP measurements were determined by standardized automated measurements, estimated glomerular filtration rate (eGFR) by the CKD Epidemiology Collaboration equation, and genotypes by Affymetrix SNP Array 6.0. Genotype-phenotype association analysis was performed by analysis of covariance and logistic regression models Results: The number of subjects with rs4293393-genotype AA, AG, and GG were 1038 (66.7 %), 416 (29.6 %) and 57 (3.7%), respectively. Carriers of the G-allele exhibited significantly lower serum creatinine levels compared to non-carriers (AA, 0.91 mg/dl, CI: 0.90 – 0.92 vs. AG, 0.88 mg/dl, CI: 0.87–0.90 vs. GG, 0.88 mg / dl, CI: 0.84–0.93; P = 0.010). G-allele carriers had significantly higher eGFR values (AA, 76.4 ml/min pro 1.73 m 2, CI: 75.7–77.2 vs. AG, 78.4 ml/min pro 1.73 m 2, CI: 77.3–79.5 vs. GG, 78.5 ml/min pro 1.73 m 2, CI: 75.4–81.7; p = 0.010) and a lower risk of chronic kidney disease (OR: 0.651 [95% CI: 0.43–0.98], P = 0.038). UMOD genotypes were not associated with BP, diagnosis of hypertension or with parameters of cognitive function and physical performance Conclusions: These findings corroborate previous findings on the role of UMOD for renal function in the elderly. However, our data reveal no association between UMOD variants and BP or parameters of fitness in a cohort of elderly subjects in a community-based cohort in Germany.